123 LEVELS OF PHYSICAL PERFORMANCE AND PHYSICAL ACTIVITY IN OLDER ATTENDEES AT A BONE HEALTH CLINIC. (25th October 2022) - McDonagh, L; McCarroll, K; Lannon, R; Cunningham, C; Connolly, K; Murphy, N; Horgan, F
Abstract: Background: Osteoporosis and sarcopenia are two common conditions seen in community-dwelling older adults. Limited information on physical performance and activity exists in older adults at risk of osteo-sarcopenia. The aim of this study was to examine levels of physical performance and physical activity in patients attending a bone health clinic. Methods: A cross-sectional study was conducted. Community-dwelling older adults attending a bone health clinic in an acute Irish hospital were invited to participate. Primary outcome measures for physical performance and activity were: grip strength, the Short Physical Performance Battery (SPPB), the Timed Up and Go test (TUG) and the International Physical Activity Questionnaire (IPAQ). Secondary outcomes included: Bone Mineral Density T-scores, diagnosis of probable sarcopenia, osteo-sarcopenia, frailty, fractures and falls history. Results: 104 participants took part in the study. Median age was 76 (IQR 12), ranging from 65 to 91 years. Females accounted for the majority (88.5%) of recruited participants. Osteoporosis was present in 63% and osteopenia in 31%. Low physical activity levels were identified in 29%. Probable sarcopenia ranged from 17 to 37%. Osteo-sarcopenia was identified in 9 to 33% depending on four possible definitions. The most common associations with osteo-sarcopenia were frailty (CFS) and low BMI. Using reduced multivariate regression analysis, physical performance (grip strength, SPPB, TUG) and physical activity (IPAQ) were negatively associated with increased age, comorbidities, frailty and falls. Increased age was associated with all four variables analysed. Comorbidities was associated with grip strength (p=0.005), SPPB (p=0.01), TUG (p=0.041). Frailty (CFS) was associated with SPPB (p< .001), TUG (p< .001), and IPAQ (p< .001). Fall(s) history was associated with SPPB (p< .001) and TUG (p=0.028). Conclusion: A high proportion of participants were classified as having osteoporosis, probable sarcopenia and osteo-sarcopenia. Completing physical performance and activity measures could provide useful information to clinicians about patients and their potential risks/deficits.